Optimization Potential of Sentani Lake to Increase the Household Income and District Own Source Revenue of Jayapura District - Jufri -; Andi Gusti Tantu; Suryawati Salam (Postgraduate Bosowa University Publishing, 2018)
This study aimed to analyze the capacity of assimilation of water quality parameters in the Lake Sentani and identify appropriate management model in the carrying capacity of Lake Sentani. The analysis showed that a key element in the management of Lake Sentani initiated by law enforcement, Coordination area, Strengthening relationships between stakeholders, compromise the level of need and Development OBM, elements other needs are also a key element in the management of Lake Sentani is Equation vision, mission and goals against environmental improvement, and Spatial Planning, the decline in the fraction of the population increases have also impacted on the decrease in the amount of waste that KJA waste, waste of pigs, cattle waste, waste of human feces, the amount of waste, and decrease erosion effect on residential and agricultural erosion. From the results of this study concluded that, for the parameter TDS assimilation capacity of 12184.94 tons / month, BOD of 11.31973 ton / month, COD is 122.4184 tons / month, PO4 of 1.401685 tons / month, NO3 by 185,2202729 tons / month, Fe at 0.226383192 ton / month, Cl amounted 15286.18799 ton / month, SO4 amounted to 1276.118 tons / month, Zn amounted to 0.169118 tons / month, Cu of -0.06125 ton / month, Cr at 0.769953052 ton / month, and NH3 at 8.620493359 ton / month. Parameter Cu, PO4, Zn and Fe is above the value of assimilation capacity, this shows the carrying capacity of Lake Sentani have declined. Policy measures total reduction of pollutant sources is through setting migration of people coming to live in the vicinity of Jayapura and Sentani Lake, approaches to sources, law enforcement, and agricultural intensification.